الاصلاح السياسي كضمان لديمقراطية العملية الانتخابية في الجزائر _دراسة حالة للانتخابات التشريعية سنة 2012_ - مزغيش سمية (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تهدف هذه الدراسة الى التركيز على مجموع الإصلاحات السياسية المتخذة من طرف الحكومة الجزائرية، التي حاولت إعطاء مصداقية للعملية الانتخابية من خلال ما جاء به القانون (01-12) وهذا قبل إجراء الانتخابات التشريعية بتاريخ 10 ماي 2012 وذلك من خلال توسيع المجال لتأسيس الأحزاب الديمقراطية، وتفعيل لدور الاعلام وتحريره من مختلف القيود التي كانت مفروضة عليه، بالإضافة الى تمكين المرأة في الحياة السياسية. من خلال الإجراءات السابق ذكرها يمكن استخلاص مجموعة من النتائج من بينها بروز هذه الإصلاحات السياسية على شكل مجموعة من الضمانات المقدمة من طرف الحكومة الجزائرية لجعل الانتخابات عملية ديمقراطية تتوافق مع الأهداف الحقيقية للعملية الانتخابية أساسها التمثيل والمشاركة. This study aims to focus on the total political reforms taken by the Algerian government Which tried to give credibility to the electoral process through what was stated in the law (01-12), This is before the legislative elections are held on May 10, 2012, And that by expanding the field for the establishment of democratic parties and activating the role of the media and liberating it from the various restrictions that were imposed on it. In addition to empowering women in political life. Through the aforementioned measures a set of conclusions can be drawn, including the emergence of these political reforms in the form of a set of guarantees provided by the Algerian government. To make elections a democratic process consistent with the real goals of the electoral process based on representation and participation.